A Review on Micropropagation Culture Method - Gupta, Nikita; Jain, Vidhi; Joseph, Merin Rosy; Devi, Siwani (Asian Journal of Pharmaceutical Research and Development, 2020)
Micropropagation is a vegetative propagation conducted under controlled and aseptic conditions in the microenvironment of the culture vessel, which have the all growth requirements of a plant in the natural conditions. Recently different techniques of propagation have been developed which could facilitate large scale production of plants and for the improvement of the species. An overview on the in vitro propagation via meristem culture, callus culture and protoplast culture etc. are presented here. Today micropropagation techniques are applied in order to produce large numbers of new high-quality plants in a relatively short time and space, in low cost and can also be preserved.